Genomic Characterization of Antimicrobial Resistance Genes in Pasteurella multocida Isolates from East Nusa Tenggara and Lampung, Indonesia - Prihandani, Sri Suryatmiati; Wibawan, I Wayan Teguh; Noor, Susan Maphilindawati; Ekawasti, Fitrine; Khairullah, Aswin Rafif; Purba, Hastuti Handayani S.; Puarada, Alif Rahman Rohim; Safika, Safika (Jurnal Medik Veteriner, 2025)
Haemorrhagic Septicaemia (HS) is a devastating disease affecting cattle and water buffaloes in Indonesia, causing annual economic losses in livestock industries, particularly in Asia, Africa, and the Middle East. Pasteurella multocida, the causative agent of the disease, has shown increasing antimicrobial resistance, complicating treatment efforts. Therefore, this study aims to provide the first genomic analysis of P. multocida isolates from different Indonesian provinces, focusing on genes conferring resistance to beta-lactam antibiotics based on Whole Genome Sequencing (WGS) results. Genomic data can be used to confirm the results of phenotypic antibiotic resistance testing. P. multocida isolates analyzed in this study were sourced from the Indonesian Research Center for Veterinary Science (IRCVS) collection, which included 2 samples originating from different geographic locations within Indonesia. The samples were subjected to biochemical, molecular, and antimicrobial susceptibility testing. WGS was performed using Oxford Nanopore Technologies (ONT) with subsequent bioinformatics analysis for genome assembly and resistance profiling. Phenotypic analysis showed significant variations between the isolates. The NTT isolate showed resistance to Penicillin, while the Lampung 2952 remained susceptible in the disk antibiotic test. Genome sequencing revealed extensive resistance determinants, including β-lactamase genes (blaZ, blaR1) in the NTT isolate, correlating with its phenotypic resistance. The high-quality genome assemblies (N50: 17,225 bp for NTT; 12,662 bp for Lampung 2952) enabled comprehensive resistome characterization, identifying more than 22 resistance genes in each isolate, including novel variants not previously reported in Indonesian strains. Therefore, this study provides the first genomic and resistance analysis based on Whole Genomic Sequencing data of Indonesian P. multocida isolates. The results show the urgent need for enhanced surveillance and prudent antimicrobial use in livestock management.